An Islamic Response to Capitalism: A Study of Mawdūdī’s Writings on Islamic Economics - Razzaq, Zain; Nawaz, Rab (Al-Irfan, 2023)
Sayyid Abul A‘lā Mawdūdī (1903-79) is recognized as one of the foremost scholars and religious revivalists of the twentieth century. Mawdūdī is widely famous for his views on Islamic economics as he is for his discourses on the Islamic state. He was not a professional economist but a reformer who proposed the foundations of an Islamic state economy in keeping with the central objective of Sharī‘ah rather than systemizing a scientific discipline. He mostly wrote on Islamic economics in the context of his discussion about dīn and the Islamic state. It may be said that in the Indian subcontinent, he played a leading role in developing the economic system of Islam as a distinct discipline. This paper aims to analyze the economy of the Islamic state vis-à-vis capitalism, employing Maududi’s writings as primary sources. This paper is divided into three sections, the first section of which deals with Mawdūdī’s conception of capitalism. The second section of the paper examines Mawdūdī’s critique of capitalism to identify the flaws of the capitalist economy. The final section section involves identifying the principles of Islamic economics proposed by Mawdūdī as an alternative to capitalism.